Pemanfaatan Brotowali sebagai Bahan Dasar Pembuatan Pestisida Nabati - Martha, Rahma Diyan; Kholifah, Siti Nurriyatul; Nurjanah, Mutia Hariani (Universitas Pahlawan Tuanku Tambusai, 2025)
The intensive use of chemical pesticides in the agricultural sector has raised serious concerns due to their adverse effects on human health and the environment. In response to this issue, the development and application of botanical pesticides offer a safer and more sustainable alternative. This community engagement initiative was conducted with the objective of enhancing the knowledge and practical skills of farmers in Wates Village regarding the utilization of Brotowali as a raw material for botanical pesticide production. The implementation of the program comprised three main stages: preliminary coordination and needs assessment, educational outreach and training, and evaluation through pre- and post-intervention testing. The results indicated a substantial improvement in participants’ understanding, with correct responses increasing from 30% in the pre-test to 85% in the post-test. Furthermore, qualitative reflections revealed a high level of participant interest in independently producing and applying botanical pesticides using locally available resources. This initiative underscores the effectiveness of participatory and educational approaches in fostering sustainable agricultural practices and promoting the adoption of indigenous plant-based pest control methods.